2002
DOI: 10.1046/j.1471-0528.2002.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised clinical trial comparing the effects of delayed versus immediate pushing with epidural analgesia on mode of delivery and faecal continence

Abstract: Objective To assess the effects of delayed vs immediate pushing in second stage of labour with epidural analgesia on delivery outcome, postpartum faecal continence and postpartum anal sphincter and pudendal nerve function. Design Prospective, randomised, controlled trial.Setting Tertiary referral maternity teaching hospital.Population One hundred and seventy nulliparous women randomised at full dilatation to immediate or delayed pushing. Methods A total of 178 nulliparous women, all with continuous epidural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 32 publications
2
38
0
2
Order By: Relevance
“…These time intervals were chosen as surrogates for intent regarding management of the second stage; sixty minutes was felt to be an amount of time in which it was likely that the patient or provider intentionally waited to initiate pushing, rather than delayed for logistical or personnel reasons. This definition of delayed pushing is consistent with prior published reports on this topic 14,16 and with the definition used in a current National Institutes of Health-sponsored multicenter randomized trial of immediate versus delayed pushing. 18 Women who initiated pushing between 31 and 59 minutes after achieving the second stage were excluded from the primary analysis due to lack of information about the reason why pushing was intermediately delayed; this population was included in a sensitivity analysis.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…These time intervals were chosen as surrogates for intent regarding management of the second stage; sixty minutes was felt to be an amount of time in which it was likely that the patient or provider intentionally waited to initiate pushing, rather than delayed for logistical or personnel reasons. This definition of delayed pushing is consistent with prior published reports on this topic 14,16 and with the definition used in a current National Institutes of Health-sponsored multicenter randomized trial of immediate versus delayed pushing. 18 Women who initiated pushing between 31 and 59 minutes after achieving the second stage were excluded from the primary analysis due to lack of information about the reason why pushing was intermediately delayed; this population was included in a sensitivity analysis.…”
Section: Methodssupporting
confidence: 87%
“…9 In contrast, a meta-analysis of twelve randomized controlled trials reported delayed pushing was not associated with increased spontaneous vaginal delivery when the analysis was limited to high quality studies. 10 Randomized trials also have reported conflicting results, with some reporting decreases in time spent actively pushing, 11,12 others with no difference in time spent actively pushing or mode of delivery, 13,14 and another with a decrease in "difficult" deliveries but no difference in "nondifficult" vaginal deliveries. 15 A retrospective analysis by Frey et al reported delayed pushing to be associated with longer active pushing time, no change in or lower spontaneous vaginal delivery rate, and worse perinatal outcomes, including maternal fever and lower cord arterial pH.…”
Section: Introductionmentioning
confidence: 99%
“…In one randomized trial of delayed pushing versus immediate pushing, where there was a significant (p<0.001) decrease in the length of second stage (median [range], 120 [57-255] vs 60 [0-148] minutes, respectively), there was no significant difference in the proportion of women with postpartum fecal continence. [20] In a retrospective study, 360 primiparous women were queried regarding anal incontinence symptoms and those with a prolonged second stage of labor (n=197, >90 minutes) were compared to those with a short second stage (n=163, <30 min). With a response rate of 51%, flatal incontinence was noted in 9.1% of subjects in the prolonged second stage group compared to 15.6% in the shorter second stage group (p=0.18).…”
Section: Discussionmentioning
confidence: 99%
“…Episiotomy and/or perineal lacerations increase the mother's risk of pain, infection, and hemorrhage, and prolong recovery time (MacLeod et al, 2008). The long-term risks of fecal incontinence or pudendal nerve damage ( Fitzpatrick et al, 2002), urinary incontinence, and dyspareunia (Hall, McCraken, Osterwell, & Guise, 2003;Liebling et al, 2004) are also increased with instrumental vaginal birth.…”
Section: Episiotomy/instrumental Vaginal Birthmentioning
confidence: 99%